The impact of 4i of transformational leadership element and integrated innovation to employee performance with employee motivation as mediator - Ardi Kho; Adi Chandra; Elvitria Intan Novita; Herlina Waluyo; Jenneta Virenna Rachmad; Kevin Siddharta (Enrichment : Journal of Management, 2023)
This research examines transformational leadership 4i elements which are Idealized Influence, Inspirational Motivation, Intellectual Stimulation and Individualized Consideration combined with Integrated Innovation and their impact to organizational performance with motivation as moderator by using Bootstrapping-SEM. From the research result, all 4i of Transformational Leadership elements and Integrated Innovation give positive impact to motivation but only Idealized Influence and Inspirational Motivation significantly give positive impact to motivation, and motivation significantly give positive impact to organizational performance. Thus, for effective management, developing leadership qualities such as Idealized Influence and Inspirational Motivation is key in leading a more motivated employee and ultimately enhancing organizational productivity and performance.